PENGUATAN TATAKELOLA UKM TENUN IKAT TROSO - Hadi Ismanto (Journal of Dedicators Community, 2017)
Troso tie or Troso cloth is a Jepara weaving craft precisely from the village of Troso. Weaving craft is weaving from strands of threads of yarn or lint threads previously tied to form a particular motif and immersed in a natural dye. Until now weaving ikat troso has grown into a home industry that supports the economy of the troso village with a broader market in various regions in Indonesia, Malaysia and Brunei Darussalam. In running its business the craftsmen pay less attention to management aspect and also consistency aspect of product quality. Problems that exist in partner SMEs, among others; 1) SMEs today have difficulty recruiting employees and technology that still rely on human strength; 2) SMEs do not yet have a good financial administration system. From these problems then the solution offered as follows: 1) Modify Non-Engine Weaving Machine (ATBM) into a semi-machine loom (ATSM); 2) Developing the Financial Administration System. The solutions offered have a purpose: 1) Product Quality Improvement; 2) Minimizing the Dependency of Skilled Weaving and For Increasing Productivity of the Produce Cloth; 3) Facilitating the Craftsman in Preparing and Controlling the Work and Giving Ease In Taking Decision.